2015
DOI: 10.1007/s10853-015-9069-y
|View full text |Cite
|
Sign up to set email alerts
|

Track formation in III-N semiconductors irradiated by swift heavy ions and fullerene and re-evaluation of the inelastic thermal spike model

Abstract: International audienceAlN, GaN, and InN were irradiated at room temperature with monatomic swift heavy ions and high-energy fullerenes. Ion track formation was studied using transmission electron microscopy in both plane view and cross-sectional modes. A full experimental description of ion track formation in these compounds is presented. AlN shows a remarkable resistance towards track formation; InN is the most sensitive and shows partial decomposition, likely into N-2 and metallic clusters; the overlapping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 83 publications
4
61
1
2
Order By: Relevance
“…1. This value is far below that deduced by Shall et al [26], 15 nm, in crystalline germanium c-Ge, i.e. in good consistency with (λamorphous < λcrystalline).…”
Section: Numerical Results and Discussionsupporting
confidence: 78%
“…1. This value is far below that deduced by Shall et al [26], 15 nm, in crystalline germanium c-Ge, i.e. in good consistency with (λamorphous < λcrystalline).…”
Section: Numerical Results and Discussionsupporting
confidence: 78%
“…In contrast, the electronic parameters are yet unknown. In the context of the TTM, the conduction electrons are usually assumed to have a metal-like behaviour and C e and K e are considered constant (e.g., 18,19,22 ) or have a linear dependence with the electronic temperature, T e 13 . However, it has been shown that even for pure metals, this approximation can be misleading 37 , and even more questionable for semiconductors as discussed for SiC 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, conflicting reports have been published on the matter of strongly ionising radiation effects on GaN. Sall et al 19 used transmission electron microscopy (TEM) to study GaN films irradiated with SHI and concluded that those are capable of amorphising the crystal. This result opposes the one obtained previously by Kucheyev et al 20 , who used Rutherford backscattering spectrometry/channelling (RBS/C) to show that even when GaN films are irradiated with high fluences (above 1 × 10 12 cm −2 ), they presented a defective but still crystalline structure.…”
mentioning
confidence: 99%
“…L'augmentation de la fluence conduità l'augmentation de la concentration de défauts et la croissance de la zone endommagée depuis la surfaceà travers l'épaisseur du film, avec une saturationà forte fluence (80 % de décanalisation observée en RBS-c [21]). En considérant un rayon de trace d'environ 2,4 nm pour les ions uranium dans le GaN [17], le recouvrement des traces latentes laissées par ces ions dans le matériau a lieu dès une fluence de 10 13 ions/cm 2 , et aboutit rapidementà une saturation du dommage et un désordre cristallin homogène sur uneépaisseur importante de l'ordre de 2.5 µm [22].…”
Section: Résultats Et Discussionunclassified
“…Sa loi de comportement, tout comme l'évolution de son module et de sa dureté, plus stables en fonction de la profondeur de pénétration, rappelle le comportement d'un matériau amorphe. Même s'il aété montré que le GaN après bombardement ionique reste cristallin, les traces latentes créées par le passage des ions lourds peuvent comporter de petites poches de matière amorphes [21][22][23]. Dans un régime de recouvrement des traces, chaque nouvel ion qui traverse apporte une nouvelle partie amorphe, et augmente la fraction de matière amorphe des films, sans toutefois aboutirà la création de zones totalement amorphes [22,23] : la réponse du GaN tend alors vers celle d'un matériau amorphe.…”
Section: Résultats Et Discussionunclassified